Control interno contable y su incidencia en la calidad de la información financiera a la empresa Corporación Impactex Cia.Ltda - Sagñay Patajalo, Martha Cecilia (2019)
Internal control has become one of the most important pillars to achieve the goals of any entity regardless of its size or activity. By this, the investigation was carried out about the internal accounting control and its incident in the quality of the financial information of the Corporation Impactex Ltda, since there have been deficiencies in their accounting procedures, caused by inadequate control and lack of training of personnel who are working in the financial department; those aspects could cause inaccuracies or error at the moment of registering the transactions of the economic and financial operations. So the present project has as aim to establish a methodology of evaluation the system of internal accounting control at the financial department. Regarding the methodology, descriptive, explanatory, documentary and field investigation were used which helped the development of this investigation; furthermore, the most common techniques such as the survey and the interview were applied, which application allowed the permanent collection of information. The results through the methodology for the evaluation of the internal accounting control based on the model COSO II or COSO "ERM" (Enterprise Risk Management) to the financial department will allow to detect, to control and to mitigate the risks in a preventive way through improvement actions that face the detected deficiencies, converting the weaknesses in strength and the threats in opportunities to increase the level of confidence in each one of its activities that will optimize the economic and material resources. Finally, the impact within the financial department was to provide an instrument that allows self-evaluations to verify the functioning of the internal control system (ICS) in such a way that the personnel have knowledge of the risks or opportunities in the environment, thus improving their job performance in the preparation and presentation of financial statements thus ensuring the reasonableness of financial information, and therefore will allow clients, providers and financial institutions to continue confiding in and supporting the company so that it continues to be profitable.